2021
DOI: 10.1001/jamanetworkopen.2021.27387
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Serum Glucose and Kidney Disease Progression Among Patients With Diabetes

Abstract: IMPORTANCE The appropriate target of glycemic control in diabetic kidney disease is unclear. OBJECTIVE To investigate optimal on-treatment glycemic levels associated with slowing of diabetic kidney disease progression. DESIGN, SETTING, AND PARTICIPANTS This retrospective cohort study was conducted using nationwide Korean cohorts from the National Health Information Database from 2005 to 2019. Included individuals were adults with diabetes using antihyperglycemic agents with and without chronic kidney disease (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 27 publications
1
3
0
Order By: Relevance
“…On the other hand, a high risk for ESKD was observed in individuals whose baseline FG levels were <100mg/dL or ≥180 mg/dL. These findings were consistent with another nationwide cohort study of Koreans with diabetes using GLMs [31], suggesting that intensive glucose control might not necessarily diminish the progression of established diabetic kidney disease.…”
Section: Kidney Outcomes and Long-term Glucose Variabilitysupporting
confidence: 85%
“…On the other hand, a high risk for ESKD was observed in individuals whose baseline FG levels were <100mg/dL or ≥180 mg/dL. These findings were consistent with another nationwide cohort study of Koreans with diabetes using GLMs [31], suggesting that intensive glucose control might not necessarily diminish the progression of established diabetic kidney disease.…”
Section: Kidney Outcomes and Long-term Glucose Variabilitysupporting
confidence: 85%
“…Diabetic nephropathy is the leading cause of ESRD in adults 23 24. In patients with diabetic CKD, blood glucose levels are associated with poor outcomes such as serum creatinine doubling, ESRD and mortality, and intensive glycaemic control could reduce these risks 25–29. Additionally, several studies have demonstrated that certain levels of dyslipidaemia is independently associated with rapid renal progression, KRT, all-cause mortality and cardiovascular death in predialysis patients 30–33.…”
Section: Discussionmentioning
confidence: 99%
“…Spain, 23 Norway, 24 and the United Kingdom 25 reported low levels of screening (≤32% screening). In smaller countries, with centralized medical delivery systems, for example, Denmark 26 and South Korea, 27 screening rates have reached ∼80% in the past few years. Regarding automated laboratory ordering, little information is available in the medical literature.…”
Section: Discussionmentioning
confidence: 99%